Influence of Social Media Complaints on Customer Service Quality Amongst Selected Banks in Lagos state, Nigeria - Ezurike, Nduneche (British Journal of Marketing Studies, 2024)
Financial institutions are increasingly leveraging social media not only for customer interaction but also for managing their daily operations. In the banking sector, the utilization of social media for addressing customer complaints is rapidly gaining traction. Consequently, customers are increasingly embracing social media platforms due to their ability to provide prompt responses to their inquiries and complaints. This study seeks to examine the influence of social media complaints on customer service quality among selected banks in Lagos state, Nigeria. The study was anchored on the Service Recovery Paradox, while the descriptive survey research design was adopted in this study. The Topman’s formula for unknown population was used to calculate a sample size of 250 respondents and the available sampling technique was used to select respondents sampled for this study. Findings revealed that majority of the respondents sampled for this study utilize social media extensively to voice their concerns or complaints about banking services. Findings further revealed that a substantial proportion of respondents sampled for this study believes that banks effectively respond to customer complaints raised via social media platforms. The study recommends that banks should provide comprehensive training to customer service representatives to equip them with the skills and knowledge necessary to effectively handle complaints and resolve issues raised on social media platforms.